The Experiences and Healthcare Needs of Families Living With Pediatric Brain Tumor: A Longitudinal Qualitative Study Protocol - Kate Young; Evonne Miller; Stuart Ekberg; Natalie Bradford (International Journal of Qualitative Methods, 2020)
For most children and adolescents diagnosed with a brain tumor, whether malignant or not, there will be an irrevocably negative impact on their life and that of their family. In Australia, 5 year disease-free survival is 76% meaning that many young people will go on to live with the negative consequences—including neurological and cognitive deficits, reduced school performance, psychological problems, and problems with peer social relationships—of the tumor and associated treatment. Little is known about the experiences and psychosocial healthcare needs of families living with brain tumor, particularly from the perspectives of children and adolescents. We will fill this knowledge gap with a multimethods approach for flexible data collection that addresses the diverse needs of children and families living with a life-threatening illness. Recruited through the largest state pediatric health service in Queensland, Australia, we will follow families from diagnosis to capture their experiences and healthcare needs as they navigate their child’s treatment and survivorship or death. Data collection methods include semi-structured interviews, virtual tours and Photovoice; all family members will be invited to participate. Reflexive thematic analysis will be used to explore the lived experiences of families, and their community and health services needs and associated facilitators and barriers to receiving such care. Our analysis will consider multiple perspectives: the individual, dynamics within each family, and patterns observed across families. This research will inform the co-design of interventions with families to address the service gaps and healthcare needs identified by participants.